2021
DOI: 10.1088/1361-6528/ac0dda
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing temperature on the optoelectronic properties of ITZO thin films

Abstract: In this work, the electrical conductivity and optical transparency of the In-Sn-Zn-O (ITZO) films annealed at different temperatures were investigated. The results show that the ITZO films transformed from amorphous phase to crystalline phase after annealed in the air. The transmittance of the films improves significantly and all exceed 88%. Meanwhile, the annealed ITZO films exhibit a significant enhancement in conductivity. In particular, ITZO film annealed at 650 °C has high electrical conductivity (∼4.94×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The bandgap ( E g ) was determined by analyzing the horizontal intercept of the linear portion in the Tauc plot from Figure f. The E g of all the films range from 3.2 to 3.5 eV, consistent with the range of E g reported for conventional ITZO films. , It is evident from the figure that the E g of the no-water film is smaller than that of the with-water film at all T A . Prior studies report that in the same material, an increase in defects typically leads to a reduction in the bandgap. However, the relationship between them is reverse in this work, as found in Figure e,f that the with-water films inhibit more band-tail and deep-level defects and demonstrate a larger E g at T A = 0, 200 °C.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The bandgap ( E g ) was determined by analyzing the horizontal intercept of the linear portion in the Tauc plot from Figure f. The E g of all the films range from 3.2 to 3.5 eV, consistent with the range of E g reported for conventional ITZO films. , It is evident from the figure that the E g of the no-water film is smaller than that of the with-water film at all T A . Prior studies report that in the same material, an increase in defects typically leads to a reduction in the bandgap. However, the relationship between them is reverse in this work, as found in Figure e,f that the with-water films inhibit more band-tail and deep-level defects and demonstrate a larger E g at T A = 0, 200 °C.…”
Section: Resultssupporting
confidence: 71%
“…The E g of all the films range from 3.2 to 3.5 eV, consistent with the range of E g reported for conventional ITZO films. 22,23 It is evident from the figure that the E g of the no-water film is smaller than that of the with-water film at all T A . Prior studies report that in the same material, an increase in defects typically leads to a reduction in the bandgap.…”
Section: Resultsmentioning
confidence: 90%
“…With a steady increase in the oxygen partial pressure, it could lead to the growth of acceptor-like deep states, which can be considered as weakly bonded excess oxygen states (O°or O − ) [40]. The increasing accepter-like deep states will trap more electrons in the channel to form ionized stable O 2− states, thus the S.S turns to increase [13]. From the change of the S.S, it can be concluded that the S.S of the device can be optimized by varying the oxygen partial pressure.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, transparent-oxide-semiconductorbased transistors have emerged as promising alternatives to the aforementioned TFTs due to its high μ FE (>10 cm 2 V −1 s −1 ), small sub-threshold swing (S.S), low off current (I off ), good stability under electrical stress and low-temperature fabrication (<250 °C) [8]. A large number of oxide semiconductors have been developed for TFT applications, including amorphous zinc-tin oxide (a-ZTO) [9], amorphous indium-zinc oxide (a-IZO) [10], amorphous indium-galliumzinc oxide (a-IGZO) [11,12] and amorphous indium-tin-zinc oxide (a-ITZO) [13,14].…”
Section: Introductionmentioning
confidence: 99%